Cystic Trigeminal Schwannoma - Cherkaoui Mandour (Romanian Neurosurgery, 2016)
Trigeminal schwannoma is the second commonest intracranial schwannoma; they remain rare. A minority exhibit cystic changes, with even fewer an intracystic fluid level. We report a case of a 45-year-old man, presented with a progressive hearing loss, worsening right-sided facial spasms and facial numbness in the region of the right trigeminal nerve. Neurological examination revealed hypoesthesia in the right facial region and intermittent rights sided hemi-facial spasms, without signs of raised intracranial pressure or achieve the mixed nerves or neurological deficit. A Magnetic resonance imaging of the brain revealed a cystic mass in the right cerebello-pontine angle with extension forward towards the cavum meckel. The patient was operated by retro sigmoid approach, with a total resection of the tumor. Intracranial cystic schwannomas constitute an uncommon subset of tumors with a distinct clinico-biological behavior. The presence of fluid–fluid levels within the tumors, although rare, confirms the cystic nature of the neoplasms. Cystic areas are usually secondary to the coalescence of mucinous or microcystic regions in Antoni B tissues. The treatment is surgical in the majority of cases and stereotactic radiosurgery has a clear role for adjuvant treatment of post-surgical recurrence of the tumor or residue.